COVID-19: Targeting Proteases in Viral Invasion and Host Immune Response - Seth, Sanchit; Batra, Jyotsna; Srinivasan, Srilakshmi (Frontiers in Molecular Biosciences, 2020)
An acute respiratory disorder (COVID-19) that accelerated across globe has been found to be caused by a novel strain of coronaviruses (SARS-CoV-2). The absence of specific antiviral drug or vaccination has promoted the development of immediate therapeutic response against SARS-CoV-2. As the increased levels of plasma chemokines, cytokines and uncontrolled influx of inflammatory cells were observed in lethal cases, the severity of the infection corresponded with the imbalanced host immunity against the virus. Tracing back the knowledge acquired from SERS and MERS infections, clinical evidence suggested similar host immune reactions and host ACE2 receptor derived invasion by SARS-CoV-2. Further studies revealed the integral role of proteases (TMPRSS2, cathepsins, plasmin etc.) in viral entry and immune system. This review aims to provide a brief review on latest research progress in identifying the potential role of proteases in viral spread, infection and combines it with already known information on the role of different proteases in providing immune response. It further proposes multidisciplinary clinical approach to target proteases specifically, by combinatorial administration of protease inhibitors. This predictive review may help in providing a perspective to gain deeper insights of the proteolytic web involved in viral invasion and host immune response.